EFESIENSI JADWAL PROYEK ACARA PERNIKAHAN MELALUI CPM (CRITICAL PATH METHOD): STUDI KASUS WISMO & AMALIA - Pesta Gultom; Betania Gulo; Delamin br Sembiring; Elizabeth Maretha Marbun; Darniati br Sitorus (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Effective time management is a critical factor in the successful execution of a wedding event. This study aims to analyze the schedule efficiency of the wedding project for Wismo & Amalia using the Critical Path Method (CPM). The method is applied to identify the critical path that determines the project duration and minimizes potential delays. Data were collected through direct observation, interviews, and documentation of the activity schedule during the preparation process. The analysis revealed that the critical path consists, MC/entertainment, rehearsal, and the event execution, with a total duration of 27 days. Non-critical activities have flexible time buffers that can be utilized to anticipate obstacles without affecting the overall schedule. These findings confirm the effectiveness of CPM in optimizing time management for small to medium-scale wedding project. The practical implication of this study is the enhancement of time control, which facilitates smooth event implementation and timely completion.